Collaboratively Developing Information Literacy Curricula for Academic Writing through Focus Groups with Romanian and American Educational Professionals - Katherine RUPRECHT (ACROSS)
Disinformation and misinformation have become increasingly alarming problems for all educators in almost every country with the rise of Internet use and social media. But how do educational professionals counter what seems like an overwhelming issue? Local and international education professionals should work together to share insight into effective methods of assisting students with the difficult task of discerning what is real and credible online. An excellent place to start with this daunting challenge is to build an information literacy curriculum that assists students with academic writing. Teaching information literacy skills in conjunction with basic academic writing skills sets students on a path to be critical thinkers and to learn how to do reliable online research.